2007
DOI: 10.5694/j.1326-5377.2007.tb01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimising collateral damage: family peer support and other strategies

Abstract: The impact on family members of mental illness in a young person is intensely distressing. Symptoms that they cannot understand, and the stigma surrounding mental illness may lead to families feeling isolated in their distress. Family carers are reassured by talking with other families who have experienced the same or similar situations. The “Families Helping Families” program at ORYGEN Youth Health trains family peer‐support workers, who are employed to provide information and support to families new to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…This can be channeled into political action through participation in family groups, such as the National Alliance on Mental Illness, which has played a strong role in obtaining legal parity of coverage for health care. As described in other studies (18,19), this study showed that families want information and support and more involvement in the care and recovery of their loved ones. Their wishes are consonant with calls by the President’s Commission for more patient- and family-centered care (29) and calls by the IOM for involving patients and families in the design, administration, and delivery of treatment and recovery services (31).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This can be channeled into political action through participation in family groups, such as the National Alliance on Mental Illness, which has played a strong role in obtaining legal parity of coverage for health care. As described in other studies (18,19), this study showed that families want information and support and more involvement in the care and recovery of their loved ones. Their wishes are consonant with calls by the President’s Commission for more patient- and family-centered care (29) and calls by the IOM for involving patients and families in the design, administration, and delivery of treatment and recovery services (31).…”
Section: Discussionsupporting
confidence: 80%
“…Focus groups have identified that families want more involvement, support, advice on managing symptoms, aid in navigating treatment systems, and contact with other families (18,19). Specifically, families requested multifamily psychoeducational groups in which patients are not present, rapid outreach after diagnosis, phone support from trained peers, and information on illness and treatment.…”
mentioning
confidence: 99%
“…). Furthermore, actively engaging parents and carers in care impacts positively on the entire family (Leggatt ; Yeun and Toumbourou ).…”
Section: Family‐inclusive Practicementioning
confidence: 99%
“…While peer support services are well developed in adult services, both for families and for primary consumers (Verhaeghe et al . 2008), so far there has been relatively little reported about the impact of peer support services for families of children and adolescents with a mental illness, despite increasing recognition of the importance and value of such services (Leggatt 2007). This study aimed to fill a gap in the literature by investigating how parents have utilized a consumer consultant support service provided in the inpatient unit of a Queensland child and youth mental health service.…”
Section: Introductionmentioning
confidence: 99%